Effectiveness of the Vahanwala method in determining sex through cheiloscopy in scanned impressions of a group of peruvian students - García Jáuregui, Lesly Yuliana (2021)
Objective: To demonstrate the effectiveness to determine sex through cheiloscopy using the Vahanwala method in scanned lip impressions at the Tupac Amaru Apurímac Secondary Training Entity for Minors in Lima, Peru in 2017. Methods: 94 lip imprint samples were collected for the study, of which 44 were from male and 50 from females. The lip prints were made using black lipstick, adhesive tape, swabs, and bond paper. After the collection, a HP Deskjet 2540 scanner was used to obtain images of the lip prints, and these were analyzed with the Adobe Photoshop CS6 program. The following aspects were recorded and evaluated; type of labial grooves, distribution of the labial commissures, lip thickness and the relationship these aspects had in the differentiation of gender. Concordance between the result of the method and the real sex of the lip print was evaluated with the statistical-kappa test. Results: 55.4% presented horizontal labial commissures in both sexes, 45.5% of the males presented medium lip thickness, while 34.0% of the females presented mixed type lip thickness. In relation to lip furrows, class IV furrows predominated in 59.2% of men, with class I and II furrows being found in 72.0% of women. Conclusions: The Vahanwala method is effective for sex determination using scanned lip impressions.